The Relationship Between Self-Confidence and Peer Social Acceptance - Chaira, Rahmatul; Taufik, Taufik (The Future of Education Journal, 2025)
This research is motivated by the large number of students who still have low levels of social acceptance who are seen in group activities in studying and playing. This condition is partly caused by students' low self-confidence. This research aims to describe: (1) students' level of self-confidence, (2) level of social acceptance from peers, and (3) the relationship between self-confidence and social acceptance from peers. This research uses a quantitative approach with a correlational type of research. The population of this study were students at SMA N 5 Pariaman and the sample was 231 students who were calculated using the Proportionate Stratified Random Sampling technique. The instruments used were a self-confidence questionnaire and a social acceptance questionnaire. Data were analyzed using average analysis, percentages and correlational analysis. Descriptive analysis was carried out using the percentage formula, while correlational analysis used the product moment correlation formula and the calculations were assisted using the SPSS version 20 for Windows program. The results of the study showed that: (1) the average achievement score for self-confidence reached 111.06 (67.31%) including moderate, (2) the average achievement score for social acceptance was 105.18 (67.86) including the moderate category. , (3) there is a significant positive relationship between self-confidence and the social acceptance of students' peers with a correlation of 0.431. Based on research findings, efforts are needed to provide counseling services in the field of social guidance by guidance and counseling teachers with material on the importance of increasing social acceptance and self-confidence. The application of information services, individual counseling services and group guidance is expected to help students increase their self-confidence and optimal social acceptance.